LEGAL MANAGEMENT STRATEGIES IN THE BUSINESS ENVIRONMENT: A PRACTICAL APPROACH TO HANDLING LEGAL RISK - Erwin; Amândio de Araújo Sarmento; Fuadah Johari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the era of globalisation and intense business competition, legal risk management is one of the main keys to ensuring the sustainability and success of a company. The study in this research uses the literature research method. The research found that the four strategies are interrelated and must be implemented simultaneously to achieve effective legal risk management. Firstly, the study revealed that the presence of a solid compliance programme is an important basis for identifying and managing legal risks. Next, it was found that technology integration helps in monitoring compliance and reacting to legal changes faster. Collaboration with legal and technology experts was found to not only provide access to specialised insights on the latest regulations, but also help in devising effective strategies to address legal risks. Finally, building a culture of compliance at all levels of the organisation is necessary to ensure successful implementation of legal strategies. The research concludes that, through the implementation of such a set of strategies, companies can reduce legal risks and their implications, help maintain reputation, and increase stakeholder trust. Hence, a comprehensive approach to legal risk management is necessary to facilitate sustainable business growth in an uncertain environment.